Optimization of Growth and Yield in Bird's Eye Chili (Capsicum frutescens L.) through Sustainable Organic Fertilization Using Banana Stem Compost and Tofu Industry Liquid Waste - Zahanis Zahanis; Fatimah Fatimah; Devi Purnamasari; Sindi Fantika (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2021)
The objective of this experiment was to investigate the interaction between the application of banana stem compost and tofu industry liquid waste on the growth and yield of Bird's Eye Chili (Capsicum frutescens L.). The experiment followed a factorial completely randomized design (CRD) with two factors: the first factor being the application of banana stem compost with four levels: 0 g/polybag, 100 g/polybag, 200 g/polybag, and 300 g/polybag; the second factor being the dosage of tofu industry liquid waste with three levels: 0 ml/L water, 50 ml/L water, and 100 ml/L water. Based on the research findings, it can be concluded that the application of 300 g/polybag of banana stem compost and 100 ml/L of tofu industry liquid waste resulted in increased fruit weight in Bird's Eye Chili, with a yield of 107.87 g.